Daerah sebagai Pihak dalam Kontrak Penanaman Modal Internasional (Studi Kasus Provinsi Aceh) - Sanusi Bintang (Jurnal Konstitusi, 2016)
Legal certainty is an important factor in developing international investment contracts in regional areas. How ever, it cannot be accomplisehed yet because of, among others, obscurance and inconsistance of laws regulating capacity to contracts for regional sub-divisions in Indonesia. The capacity to contract of the regional sub-divisions can be ascertained based on criteria of definition of the international contracts which is different from treaties, legal personality theory on the subject, and object concerning local government affairs. This article concludes that regional sub-divisions, such as Aceh Province, has capacity to be a party to international contracts, therefore, inconsistence laws should be adjusted.